Titanium Dioxide Hole-Blocking Layer in Ultra-Thin-Film Crystalline Silicon Solar Cells - Yangsen Kang; Huiyang Deng; Yusi Chen; Yijie Huo; Jieyang Jia; Li Zhao; Zain Zaidi; Kai Zang; James S. Harris (IEEE Photonics Journal)
One of the remaining obstacles to achieving the theoretical efficiency limit of crystalline silicon (c-Si) solar cells is high interface recombination loss for minority carriers at the Ohmic contacts. The contact recombination loss of the ultra-thin-film c-Si solar cells is more severe than that of the state-of-art thick cells due to the smaller volume and higher minority carrier concentration. This paper presents a design of an electron passing (Ohmic) contact for n-type Si that is hole-blocking with significantly reduced hole recombination. By depositing a thin titanium dioxide (TiO2) layer, we form a metal-insulator-semiconductor (MIS) contact for a 2 μm-thick Si cell to achieve an open circuit voltage ( $V_{oc}$ ) of 645 mV, which is 10 mV higher than that of an ultra-thin cell with a traditional metal contact. This TiO2 MIS contact constitutes a step towards high-efficiency ultra-thin-film c-Si solar cells.